An Inventory Tool for Receiving Practicum Report Based on IoT by Using ESP32-CAM and UV Sterilizer: A Case Study at Muhammadiyah University of Sidoarjo - Shinta Carolin Stevi Yanti; Indah Sulistiyowati (Journal of Electrical Technology UMY, 2022)
Currently, there are several problems related to practicum report collection inthe electrical engineering laboratory at the Muhammadiyah University of Sidoarjo. The firstproblem is the presence of crowds during practicum report collection that have theirdangers, specifically during the Covid-19 pandemic. Another problem is the absence oflaboratory assistants in the electrical engineering laboratory when there are students whowill collect reports. A tool that can receive practicum reports was made from these problems,and it can be monitored remotely by a laboratory assistant. By putting an RFID card to theRFID sensor on the box so that the solenoid can open the box door and the student can putthe report into the box. At the same time, ESP32-CAM takes pictures of students collectingthe report. Then, notification in the form of photos and student information will be sent tothe laboratory assistant through the Telegram application. After the report is placed into thebox, the UV Sterilizer will turn on to disinfect the report. The expectation of making this toolis to facilitate the collecting report process of practicum results and reduce the crowd in thelaboratory.